COMPUTER IMPLEMENTATION OF DAKYSTRE’S ALGORITHM FOR DETERMINING THE FORM OF THREAD REFILLING ON THE BASIS OF SEARCHING FOR THE OPTIMAL PATH OF THE GRAPH - SHCHERBAN, Volodymyr; ISHCHENKO, Valentin; KOLISKO, Oksana; GOLDBERG, Marjana; SHCHERBAN, Yuryj (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Minimization of thread tension during processing on technological machines allows to reduce the probability of breakage in the working area. This is achieved by optimizing the geometric parameters of the thread feed system on process equipment, namely obtaining such a broken thread shape, in which the total angle of coverage of structural structural elements of process equipment in the form of cylindrical guides and torus, elements of tensioning devices will have a minimum value. This will reduce the amount of friction between the thread and the guide surfaces and get the minimum tension in the working area. Given the large number of structural elements of the thread feed system on technological machines, their location in the plane and space, there is a need to use modern information technology. Implementing this requires the use of algorithms and computer programs to find the optimal path of the graph using the Dijkstra algorithm. Determining the tension and changes in relative tension in the refueling zones of technological machines, taking into account the specifics of the design of the thread feed system, will reduce thread breakage, optimize t Improving the process of thread processing on technological machines of light industry is to minimize tension and should be based on theoretical and experimental studies of the interaction of threads with structural elements of the feed system, including tensioning devices, breakage control and guides of large and small curvature. Imperfect shape of the thread filling line on technological machines of light industry, low quality of complex threads and yarn with increasing tension along the depth of filling leads to their breakage.hread tension in the working area of the source product.